Lisa M. Bitel, Landscape with Two Saints. How Genovefa of Paris and Brigit of Kildare built Christianity in Barbarian Europe, Oxford 2009, Oxford University Press, ss. 299. - Groń, Ryszard (Vox Patrum, 2009)
nie dotyczy